VALUE OF HUMANITARIAN CONSTITUENT IN PROFESSIONAL PREPARATION OF MANAGERS-ECONOMISTS IN HTEE (HIGHER TECHNICAL EDUCATIONAL ESTABLISHMENT) - Hrozna, N. Z. (Visnyk of Vinnytsia Politechnical Institute, 2013)
The problem of integration of humanitarian knowledge is examined in the article in the process of preparation of managers-economists in the Higher technical educational establishment and value of humanitarian (and in particular culturological constituent in professional preparation of specialists of this direction. The role of culturological and humanism approaches is determined at preparation of future managers in the sphere of economy, as well as the role of humanitarian preparation of specialists of this sphere.